"Finding" Payepot's Moccasins: Disrupting Colonial Narratives of Place. (February 2016) - Sperlich, Tobias; Brogden, Lace Marie
Using altered readings of normative, "common sense" histories, this article illustrates diverse entry points into interpreting narratives, museums, and place. It queries ways in which colonial subjectivities can be (re)produced through museum objects, collections, and displays, as well as the social engagements collectors, benefactors, curators, visitors, and others might have with them. The article revolves around a late 19th-century pair of moccasins of First Nations provenance attributed to renowned Cree Leader, Chief Payepot, housed in a rural, community museum, the Jasper Cultural and Historical Centre. By examining both the physical and metaphorical positionalities of "Chief Payepot's Moccasins" as they come to be represented through various texts and subtexts, we argue for a disruption of hegemonic settler narratives in the not-yet-post-colonial territory commonly known in contemporary nation state terms as southern Saskatchewan. This approach privileges thinking with objects in an effort to dislodge colonial assumptions about place and belonging, encouraging dialogic meaning-making about historical and contemporary life with Treaty in Western Canada.